The Perception and Degree of Adoption by Urbanites towards Urban Farming - Ivascu, Larisa; Ahimaz, David Frank*; Arulanandam, Benedict Valentine*; Tirian, Gelu-Ovidiu (MDPI, 2021)
Malaysia is not shielded from the issues of food insecurity. Despite economic progression over the past few years, food insecurity is continuing to affect several vulnerable groups (Orang Asli, elderly, students, B40). It is a growing concern that should not be taken lightly, especially with the recent rise in food prices coupled with low income among vulnerable groups and the effects of the COVID‐19 pandemic. As cities develop and expand, they stretch out and occupy former farmlands forcing farms to stop operating or move further off from the city centre. New trends like urban farming are slowly emerging, which have the potential to be a solution to the developing crises of food insecurity. This research aims to determine how relevant each of the factors, ‘confidence,’ (CF) ‘societal,’ (SC) ‘pleasantness,’ (PL) and ‘naturalness,’ (NT) are towards adopting (AD) the idea of urban farming and, if relevant, among which has the most positive impact. A mixed‐method approach was used to obtain quantitative and qualitative data. One hundred and thirty‐three responses were recorded and used (a significant sample size according to the G‐power software). The validity and reliability of the data were also tested to affirm their quality and relevance according to the factors. The main findings revealed that ‘pleasantness’ and ‘confidence’ were strong factors for adopting urban farming, in line with Cohen’s R Square of more than 32%, which signifies a high impact toward influencing adoption. In addition, qualitative analysis shows that while positive outcomes complemented the quantitative study, practical constraints were highlighted. These constraints were space, time, supply chain, resources, tools, community and government support. Hence, this study provides two significant contributions to regulators and policymakers on urban farming (further explained in the discussions section).